Religious Discourse and the Public Sphere in Contemporary Pakistan = Discours religieux et sphère publique dans le Pakistan contemporain - Zaman, Muhammad Qasim (Revue des mondes musulmans et de la Méditerranée, 2008)
This article examines some of the ways in which the traditionally educated Muslim religious scholars, the `ulama, of Pakistan have articulated their conceptions of the Islamic scholarly tradition and how their modes of discourse compare and compete with those of other religious intellectuals. Focusing on extensive debates in Pakistan on whether the Qur’an’s prohibition of usury (riba) also covers modern forms of financial interest, the article analyses facets and consequences of the “incommensurability” between the `ulama’s styles of discourse and those of their modernist critics. Efforts to remedy this incommensurability have had mixed results, shedding considerable light as much on how the `ulama have continued to defend their authority in the public sphere as on how their modernist challengers have fared in Pakistan.